The Heroine Concept in a Filipino Graphic Narrative - Estrella T. Arroyo (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
This study explored the concept of “HEROINE” in the context of “Darna,” a Filipino graphic narrative written by Mars Ravelo that was first published on May 13, 1950 by Filipino Komiks. Extracted from the 27 episodes of “Darna” are realities of experience as well as innuendos related to the real character of Darna, the super heroine. Further, the study delved into a deeper meaning of heroine beyond its lexical meaning. As a result, the researcher formulated her own definition of “HEROINE” as “Humaneness and Equanimity in Reimagining Optimistic, Iconic, Novel, and Empowered” persona, which led to the findings that, indeed, Darna has reached her apotheosis as a superheroine. These insights were not fathomed had it not been for the researcher’s focus on close reading, application of Expressive Realism, and “Argustic” reading. Keen eyes are needed to enjoy reading a graphic narrative which is both visual and verbal. The study proved that in Philippine society, Darna is the most accepted, loved and idolized Filipino icon as savior of a devastated and crippled society after World War II. Lastly, it is aimed that this humble analysis will put itself into the realm of a body of Pop Literature and the Humanities.